Global maths [disket] (Derbyshire, Eng. : TopClass Technology, 1994)
V.1. Global DMS : single user -- v.2.-v.5. Global maths : complete AT2-AT5 -- v.6. Global maths : install disk -- v.7. Global maths : supplementary disk